IMPLEMENTASI STRATEGI PEMBELAJARAN PAI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMP NEGERI 14 BANDA ACEH - Bahri, Sari Pitri (Majelis Pendidikan Aceh, 2023)
In the era of digitalization, Islamic religious education teachers must be able to use technology and design learning strategies to improve the quality of learning, but in reality, there are Islamic religious education teachers who do not utilize technology in the learning process and strategies that are not planned so that learning is not directed and students become passive. The aim of this research is to determine the implementation of Islamic religious education learning strategies in the digital era and to determine the strategies of Islamic religious education teachers in improving the quality of learning. The research method used is a descriptive qualitative method, with data collection techniques of observation, interviews and documentation. The results of this research are the implementation of learning strategies for Islamic religious education in the digital era. The teacher uses technology in delivering learning material through learning media, then to improve the quality of learning, Islamic religious education teachers use three strategies, namely organizing strategies, delivery strategies, and management strategies.